The PESERA-DESMICE Modeling Framework for Spatial Assessment of the Physical Impact and Economic Viability of Land Degradation Mitigation Technologies - Fleskens, Luuk; Kirkby, Mike J.; Irvine, Brian J. (Frontiers in Environmental Science, 2016)
This paper presents the PESERA-DESMICE integrated model developed in the EU FP6 DESIRE project. PESERA-DESMICE combines a process-based erosion prediction model extended with process descriptions to evaluate the effects of measures to mitigate land degradation, and a spatially-explicit economic evaluation model to evaluate the financial viability of these measures. The model operates on a grid-basis and is capable of addressing degradation problems due to wind and water erosion, grazing and fire. It can evaluate the effects of improved management strategies such as maintaining soil cover, retention of crop residues, irrigation, water harvesting, terracing and strip cropping. These management strategies introduce controls to various parameters slowing down degradation processes. The paper first describes how the physical impact of the various management strategies is assessed. It then continues to evaluate the applicability limitations of the various mitigation options, and to inventory the spatial variation in the investment and maintenance costs involved for each of a series of technologies that are deemed relevant in a given study area. The physical effects of the implementation of the management strategies relative to the situation without mitigation are subsequently valuated in monetary terms. The model pays particular attention to the spatial variation in the costs and benefits involved as a function of environmental conditions and distance to markets. All costs and benefits are added to a cash flow and a discount rate is applied. This allows a cost-benefit analysis to be performed over a comparative planning period based on the economic lifetime of the technologies being evaluated. It is assumed that land users will only potentially implement technologies if they are financially viable. After this framework has been set-up, various analyses can be made, including the effect of policy options on the potential uptake of mitigation measures and an analysis of where cost-effectiveness is highest. Apart from model description, we present case studies of the use of the framework to illustrate its functioning and relevance for policy-making.